Development, implementation and initial feasibility testing of the MediEmo mobile application to provide support during medically assisted reproduction. Issue 5 (26th March 2022) - Robertson, I; Harrison, C; Ng, K Y B; Macklon, N; Cheong, Y; Boivin, J
Abstract: STUDY QUESTION: Is it possible to develop a patient smartphone application for medically assisted reproduction (MAR) that is acceptable to patients and fertility staff? SUMMARY ANSWER: Staff and patients responded positively to the MediEmo smartphone application, perceiving it to be acceptable and feasible to implement in a busy clinic. WHAT IS KNOWN ALREADY: Digital tools are increasingly popular to provide practical, administrative and psychological support alongside medical treatments. Apps and other digital tools have been developed for use alongside MAR but there is very limited research on the development or acceptability and feasibility of these tools. STUDY DESIGN, SIZE, DURATION: Mixed methods research. This article outlines the development phase of the MediEmo smartphone app, which was guided by the Medical Research Council development framework for complex interventions. The resulting MediEmo app was then implemented into a single centre for MAR in the UK, acceptability evaluated and feasibility explored among 1106 potential participants undertaking IVF cycles. PARTICIPANTS/MATERIALS, SETTING, METHODS: Consultation and data collection took part at a single mid-sized urban fertility clinic. Development of the MediEmo smartphone application took place during 2013 to 2017. Implementation of the MediEmo took place from June 2017 to September 2020. The MediEmo app comprises three functions (six features) namely medication management (medication timeline, messaging), mood management (emotional tracking, coping support) and functional support (frequently asked questions, symptom checker). Data on age, fertility diagnosis, anti-Müllerian hormone level were collected about the users of the MediEmo in addition to MediEmo usage data and attitudes towards the MediEmo smartphone application. MAIN RESULTS AND THE ROLE OF CHANCE: Informed by the developmental process described, MediEmo is an app combining patient medication diary management and ease of integration into clinic systems with emotional support, emotional tracking and data capture. This study demonstrates acceptability and feasibility of MediEmo, with good uptake (79.8%), mood data sensitivity and reliability and positive feedback. LIMITATIONS, REASONS FOR CAUTION: Single centre, small number of users in questionnaire studies. WIDER IMPLICATIONS OF THE FINDINGS: The findings suggest smartphone apps can contribute to fertility care and that patient engagement is high. Evaluation of any apps introduced into clinical pathways should be encouraged to promote development of the most useful digital tools for fertility patients. STUDY FUNDING/COMPETING INTEREST(S): This research did not receive any specific grant from any funding agency in the public, commercial or not-for-profit sector. Outside of the submitted work, J.B. reports personal speaker fees from Merck KGaA, Darmstadt, Germany, Merck AB an affiliate of Merck KGaA, Darmstadt Germany, Theramex, MedThink China, Ferring Pharmaceuticals A/S, grant from Merck Serono Ltd, outside the submitted work and that she is co-developer of Fertility Quality of Life (FertiQoL) and MediEmo app; N.M and C.Y are minority shareholders and J.B.'s University (Cardiff University) owns one third of shares. None of the shareholders benefitted financially from MediEmo. I.R., C.H. and K.Y.B.N. declare no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.